Ayurvedic metal nanoparticles could be novel antiviral agents against SARS-CoV-2 - Sarkar, Prasanta Kumar (Int Nano Lett, 2021)
PURPOSE OF REVIEW: The pandemic COVID-19 has affected more than seventy million people globally. The whole world is eagerly waiting for an effective antiviral therapy to combat COVID-19, but it is yet to get. The emergence of COVID-19 makes imperative the need for safe and potent antiviral drugs. Many metal nanoparticles exhibit significant antiviral potential against many viral diseases. The Ayurvedic system of medicine is the treasure of many metal nanoparticulate drugs termed as Bhasma. RECENT FINDINGS: Gold, silver, copper, zinc and iron oxide nanoparticles are effective against coronavirus. A possible mechanism of action of the metal nanoparticles against coronavirus is a disruption of outer layers of coronavirus. Swarna Bhasma, Rajata Bhasma, Tamra Bhasma and Yashada Bhasma are recommended for COVID-19 treatment due to the ability to reduce the plasma interleukins, interferons and TNFα levels. SUMMARY: The Ayurvedic Bhasma preparations are unique metal nanoparticles. These metal nanoparticles are safe, stable in solid state and are having excellent biological activities. Ayurvedic metal nanoparticles, Swarna Bhasma, Rajata Bhasma, Tamra Bhasma and Yashada Bhasma could be proved as novel antiviral agents against SARS-CoV-2 for their anti-inflammatory, immunomodulatory, antiviral and adjuvant activities.